THE ANALYSIS OF THE SACRAL OBJECTS ON THE TERRITORY OF THE TITEL MUNICIPALITY - Todorov, Predrag; Mijuk, Nenad; Tošić, Teodora (The Business of Tourism, 2021)
Abstract: Sacral objects or sanctities represent the buildings used for religious or ritual purposes. The territory of the Titel municipality includes sacral objects built as the consequence of certain historical events on this territory. All of the objets were built in the period of between 18th and 20th century and some were declared the cultural monuments. In order to assess the value of sacral buildings on the territory of the municipality of Titel, from the point of view of tourism, it is necessary to perform their complex analysis, determine the significance for this and wider area, determine the current situation and possible opportunities for better promotion, evaluation and overall assessment.
Keywords: The Titel municipality; sacral objects; tourist valorization